2020
DOI: 10.15244/pjoes/115868
|View full text |Cite
|
Sign up to set email alerts
|

Can Smart Waste Bins Solve the Dilemma of Household Solid Waste Sorting in China? A Case Study of Fuzhou City

Abstract: The growing amount of waste generated and the commensurate environmental pollution in developing countries have attracted increasing attention. Traditional ways of non-classified waste disposal are threatening the sustainable development of the economy and environment. China, with its economic development and process of urbanization, has come to produce the largest amount of household solid waste (HSW) in the world since 2004, and the amount of waste is increasing every year [1]. By 2030, the annual

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…With the increased participation of property service enterprises, reward and penalty measures for residents can be effectively implemented. Residents will choose classification behavior to avoid penalty or get reward [ 72 ], thus they quickly evolve into classification behavior when property service enterprises' intention to actively participate in management increases. When property service enterprises actively participate in waste separation management, the pressure on government can be relieved.…”
Section: Discussionmentioning
confidence: 99%
“…With the increased participation of property service enterprises, reward and penalty measures for residents can be effectively implemented. Residents will choose classification behavior to avoid penalty or get reward [ 72 ], thus they quickly evolve into classification behavior when property service enterprises' intention to actively participate in management increases. When property service enterprises actively participate in waste separation management, the pressure on government can be relieved.…”
Section: Discussionmentioning
confidence: 99%
“…To strengthen the sustainability of urban villages, it is critical to nurture the participation space in which affluent community residents are able to contribute. As the nationwide campaign continues [51], the Chinese government has put more efforts to solve serious environmental problems. This is an important lesson learned not only applicable to urban village management, but could also be transferable to environmental management in formal settlements.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Third, facility factors are generally related to the convenience of performing waste separation, such as infrastructure, distance to the recycling station, and temporary space for waste. Most studies showed that facility factors positively affected residents' WSB [24][25][26]. For example, Ma et al [27] found that infrastructure had an indirect influence on residents' WSB through the mediating role of perceived cost.…”
Section: Literature Reviewmentioning
confidence: 99%